Leadership in Action : Issues and Observations - Making Leadership a Reality - Fulbright, Harriet (Center for Creative Leadership, 2006)
This article is the text of a graduation speech that Harriet Fulbright gave on May 23, 2006, at the Early College of Guilford, an advanced-placement public high school in Greensboro, North Carolina.